Bat diversity in Sitio Guillan, Barangay Mansawan (Nueva Vista), Philippines - REAH CARL B. BATERNA; ALLYSA MAE B. RAMOS; DENMAR D. MAGSALAY (Biodiversitas Journal of Biological Diversity, 2025)
Abstract. Baterna RCB, Ramos AMB, Magsalay DD. 2025. Bat diversity in Sitio Guillan, Barangay Mansawan (Nueva Vista), Philippines. Biodiversitas 26: 4898-4907. Bats are essential components of tropical ecosystems, functioning as pollinators, seed dispersers, and natural pest regulators. However, their populations are increasingly threatened by habitat loss, hunting, and human disturbance, particularly in regions where survey data remain scarce. The Philippines, recognized as a global biodiversity hotspot, harbors 73 bat species, including many endemics, yet localized assessments in Mindanao remain limited. This study assessed bat species diversity across an elevational gradient in Sitio Guillan, Barangay Nueva Vista, Don Victoriano Chiongbian, Misamis Occidental, Philippines, situated within the buffer zone of Mt. Malindang National Park. Sampling was conducted in January and April 2024 using mist-netting and the capture-mark-release method over 360 net-hours at three sites ranging from 1,042 to 1,241 m asl. A total of 134 individuals representing seven species from three families were documented. Five species were fruit bats (Cynopterus brachyotis, Rousettus amplexicaudatus, Haplonycteris fischeri, Ptenochirus jagori, P. minor) and two were insectivorous bats (Hipposideros diadema, Rhinolophus subrufus). Of these, three species were Philippine endemics and one was Mindanao-endemic. Conservation assessments indicated six species as Least Concern and one as Data Deficient. Site 1, located near a cave system, exhibited the highest species richness and diversity (H?: 1.642), while Site 3, dominated by vegetable plantations at higher elevation, showed reduced diversity. These findings provide critical baseline information on bat assemblages in Misamis Occidental, highlighting the ecological value of caves and surrounding forests as key habitats. Strengthening conservation measures in buffer zones is essential to mitigate habitat disturbance, safeguard endemic populations, and enhance sustainable biodiversity management in northern Mindanao.